Analysis of the Behavior of Health Students and Non-Health Students Towards the Covid 19 Policy in Indonesia - Muhammad Taufiqul Akbar; Ratna Wardani (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by SARS-CoV-2 and has been designated a pandemic by WHO. The Covid-19 outbreak has spread to various countries with an increasing number of cases, so cooperation from various sectors is needed, including the role of students. The purpose of this study was to determine understanding, coping strategies, levels of compliance and adaptive behavior towards COVID-19 in health and non-health students. The research method used is analytic, cross sectional approach in comparative research with accidental sampling technique. The number of each group is 60 respondents. The results of the path coefficient analysis model I, namely understanding (x1) the level of compliance (y) obtained a score (p = 0.002), standard coefficient: 0.261, p-Values: 0.002, 95% CI: 0.133-0.588, then coping strategies (x2) against level of compliance (y) obtained score (p = 0.000), standard coefficient: 0.347, p-Values: 0.000, 95% CI: 0.228-0.641. While the results of the coefficient model II, namely understanding (x1) adaptive behavior (z) obtained a score (p = 0.233), standard coefficient: -.087, p-Values: 0.233, 95% CI: -.318-0.78, then strategy coping (x2) on adaptive behavior (z) got a score (p=0.147), standard coefficient: 0.109, p-Values: 0.147, 95% CI: -0.049-0.321, and level of adherence (y) to adaptive behavior (z) obtained a score (p = 0.000), standard coefficient: 0.655, p-Values: 0.000, 95% CI: 0.499-0.805. The results between understanding and coping strategies have a significant effect on the level of compliance because someone who has good insight and coping strategies certainly has a good level of compliance, while the results are not significant on adaptive behavior because students are still in the adaptation stage of a new life. life so that a process is needed to make it a behavior.